A three-week in-hospital multidisciplinary body weight reduction program exerts beneficial effects on physical and mental health and fatiguability of elderly patients with obesity - Guerrini Usubini, Anna; Bottacchi, Michela; Bondesan, Adele; Caroli, Diana; Castelnuovo, Gianluca; Sartorio, Alessandro (Frontiers in Aging Neuroscience, 2022)
Obesity represents one of the most serious problems of public health affecting elderly populations in an increasingly relevant way. The aim of the current study was to assess the effects of a three-week in-hospital multidisciplinary body weight reduction program (BWRP) in a sample of elderly patients with obesity on reducing body mass, improving fatigue, muscle performance, and psychological well-being. Two hundred and thirty-seven consecutive elderly in-patients with obesity (males=84; females=153; age range= 65-86 yrs; mean Body Mass Index =43.7) undergoing a three-week multidisciplinary BWRP participated in the study. Data on body mass, fatiguability (measured with the Fatigue Severity Scale, FSS), muscle performance (evaluated with the Stair Climbing Test, SCT), and psychological well-being (assessed with the Psychological General Well-Being Index, PGWBI) were collected before and after the intervention. Results showed that BWRP was capable to reduce body mass [F(1.00, 235.00)=1226.8; p<0.001; ƞ2=0.024], improve perceived fatigue [F(1,234)=296.80125; p<0.001; ƞ2=0.129], physical performance [F(1.00,158.00)=119.26; p<0.001; ƞ2=0.026], and enhance psychological well-being [F(1,235)=169.0; p<0.001; ƞ2=0.103] in both males and females. Althouh it will be necessary to demonstrate with further longitudinal studies whether the reported beneficial effects will be mantained over time, the effectiveness of a three-week BWRP on different aspects involved in determining a level of autonomy and a good quality of life of elderly obese patients appears to represent a valid attempt to counteract – at least in part – the unavoidable and progressive disability of these patients.